Analisis Permintaan Konsumsi Cabai Rawit pada Rumah Tangga di Kota Mataram - Dudi Septiadi; Ni Made Wirastika Sari; Ahmad Zainuddin (Fakultas Pertanian, Universitas Timor, 2020)
This study aims to 1) analyze the characteristics of Cayenne Pepper consumers in Mataram, West Nusa Tenggara; and 2) analyze the factors that influence the demand for Cayenne Pepper in Mataram. This research was conducted at Kebun Roek Market, Pagesangan Market, and Tanjung Karang Market, Mataram, West Nusa Tenggara. Respondents were determined by quota sampling of 30 samples with accidental sampling technique. The analytical method used is a descriptive qualitative analysis method and quantitative analysis method using multiple linear regression analysis. The results showed that the consumer characteristics of cayenne pepper in this research were 100 percent female gender. The number of respondents aged 15-64 years old is 100 percent. Respondents who completed education at the Higher Education level were 63.33 percent. Respondents who have a profession as housewives are 36.66 percent. Respondents who have 3 family members are 46.66 percent. The results showed that the variable price of cayenne pepper and variable number of family members had a significant influence on the demand of cayenne pepper in Mataram.